Turning a New Page: Using Pop-up Books to Motivate Students with Learning Disabilities - Ta'ba', Yakub; Rabia, Supriyati Fatma; Yulianto, Ahmad (Utamax : Journal of Ultimate Research and Trends in Education, 2024)
Admidst the struggle of reaching a good quality of teacher competence in special education schools (Sekolah Luar Biasa/SLB), the teaching staff still must face students with learning disabilities who exihibit low levels of motivation to learn. While such description is not true for every institution, preliminary study in SLB Negeri Sorong Regency, Southwest Papua Province, proved this to be a long-term case. This study aims to solve the situation through the practice of introducing pop-up books, which are visual learning tools that are new for the selected school. A secondary aim is to thoroughly describe the factors behind the low motivation to learn for the students. The design is qualitative descriptive research, using data from observations and interviews collected from September to November 2023 (three months). With informed consent, the participants included in this study are three students, three parents, and one teacher of Phase A of the SLB Negeri Sorong Regency. The results of the new teaching media and method show an unanimously enthusiastic response from the students, turning the students’ learning atmosphere in the classroom in a more positive way. The interview further revealed factors that have caused and reinforced the low learning motivation among the students, namely: (1) the repetitive and difficult-to-follow teaching instructions and, (2) discrimination against children with learning disabilities. While the former can be effectively solved with the use of pop-up books which characteristics are not only engaging but also easy-to-follow for the students, the latter remains to be the most glaring problem. This study is significant in revealing and improving the teaching quality of special needs children in one of the few special education schools that exists in Papua.